The role of GSDMs in the immune microenvironment of prostate cancer and their impact on patient prognosis: a comprehensive analysis based on the TCGA-PRAD database - Kai Liu; Chundong D. Ji; Xuhua Qiao (Archives of Medical Science)
Introduction Material and methods Results Conclusions